2006
DOI: 10.1021/jp056258z
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation Potential Curves of Low-Lying States in Transition Metal Hydrides. 3. Hydrides of Groups 6 and 7

Abstract: The dissociation energy curves of low-lying spin-mixed states for Group 5 hydrides (VH, NbH, and TaH), as well as Group 3 hydrides (ScH, YH, and LaH), have been calculated by using both effective core potential (ECP) and all-electron (AE) approaches. The two approaches are based on the multiconfiguration selfconsistent field (MCSCF) method, followed by second-order configuration interaction (SOCI) calculations: the first method employs an ECP basis set proposed by Stevens and co-workers (SBKJC) augmented by a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 66 publications
0
23
0
Order By: Relevance
“…Other 3d transition-metal/first-row-atom diatomic species have proven to have similar challenges. [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] These studies illustrate the power of the MRCI approach, which has consistently been shown to be a reasonably robust way of investigating low-lying excited states of these systems to usually at least semi-quantitative accuracy when compared against experiment. However, the studies also demonstrate the limitations of even these very high accuracy methods, e.g.…”
Section: Introductionmentioning
confidence: 95%
“…Other 3d transition-metal/first-row-atom diatomic species have proven to have similar challenges. [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] These studies illustrate the power of the MRCI approach, which has consistently been shown to be a reasonably robust way of investigating low-lying excited states of these systems to usually at least semi-quantitative accuracy when compared against experiment. However, the studies also demonstrate the limitations of even these very high accuracy methods, e.g.…”
Section: Introductionmentioning
confidence: 95%
“…[23] a Ref. [22][23][24] [24]. Both BMK and TPSS reproduce this ordering, although the spin gap in BMK is twice larger than in WFT.…”
Section: Potential Energy Curves and Spin Gapsmentioning
confidence: 76%
“…Bauschlicher et al [20] studied the first row TM hydrides (TiH, VH, CrH, MnH, FeH, NiH) using CASSCF/SDCI method. Related method MCSCF+SOCI was used by Koseki et al to study both ground and excited state PECs of the five first row TM hydrides (ScH, TiH, VH, CrH, MnH) recently [22][23][24].…”
Section: Theoretical Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent theoretical studies include one by Balabanov and Peterson [6], in which MnH was used as a benchmark to test the reliability of new Gaussian basis sets. The dissociation curves of low-lying spin-mixed states for MnH and other group 6 and 7 transition metal hydrides have also been generated utilizing an effective core potential (ECP) approach [7]. This more recent work has also calculated a rather large ground state dipole moment of 8.0 D. Numerous density functional theory (DFT) calculations have been performed which predict the magnetic hyperfine coupling constants [8][9][10] and magnetic g-factors [11,12] for ground state MnH.…”
Section: Introductionmentioning
confidence: 99%